2021
DOI: 10.1128/spectrum.01318-21
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Studies on the Antibacterial Activity and Safety of a New Antimicrobial Peptide Dermaseptin-AC

Abstract: In this study, we discovered a new antimicrobial peptide, Dermaseptin-AC, and studied its in vitro and in vivo antimicrobial activity. These studies provide some data for finding new antimicrobial peptides for overcoming antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Analysis of the antimicrobial activity of DS-THA was carried out by determining the minimal inhibitory concentration (MIC) for E. coli and B. subtilis. For both microorganisms MIC values of 1.6 µM were determined, being consistent with previous reported values (Chen et al, 2021;Dash and Bhattacharjya, 2021) and demonstrating the production of functional target (Supplementary Figure S7). After co-incubation of VHH, a single chain antibody fragment with binding affinity towards the fluorescent protein mCherry (Wang et al, 2021), the quantitative formation of VHH-mCherry heterodimers was observed by size exclusion chromatography (SEC) analysis (Supplementary Figure S8), proving the functional fold of VHH.…”
Section: Functional Characterizationsupporting
confidence: 90%
“…Analysis of the antimicrobial activity of DS-THA was carried out by determining the minimal inhibitory concentration (MIC) for E. coli and B. subtilis. For both microorganisms MIC values of 1.6 µM were determined, being consistent with previous reported values (Chen et al, 2021;Dash and Bhattacharjya, 2021) and demonstrating the production of functional target (Supplementary Figure S7). After co-incubation of VHH, a single chain antibody fragment with binding affinity towards the fluorescent protein mCherry (Wang et al, 2021), the quantitative formation of VHH-mCherry heterodimers was observed by size exclusion chromatography (SEC) analysis (Supplementary Figure S8), proving the functional fold of VHH.…”
Section: Functional Characterizationsupporting
confidence: 90%
“…Safety is the key factor that hinders the entry of AMPs into the clinical application [ 28 , 29 ]. Therefore, we measured the hemolytic rate of Pleu and its modified peptides.…”
Section: Resultsmentioning
confidence: 99%
“…As biologists have found, insects are able to produce an immensity of biologically active substances that can serve as a model for imitation or, more importantly, a new source for obtaining medicinal preparations. We can mention that these intentions have already given results, resulting in the introduction in medical practice of food supplements or entomological drugs with various properties [17].…”
Section: General Properties / Characteristics Of Antimicrobial Peptidesmentioning
confidence: 99%